KEMENANGAN GANJAR YANG MENGAGETKAN DI DAERAH SANTRI (STUDI TENTANG PERILAKU MEMILIH MASYARAKAT DI KABUPATEN KUDUS PADA PEMILIHAN GUBERNUR JAWA TENGAH 2018) - Novia Risna Dania Fisa; Muhammad - Adnan; dewi - Erowati (Journal of Politic and Government Studies, 2023)
This research aims to reveal the factors behind the Ganjar Pranowo-Taj Yasin victory and to find out the tendency of voter behavior of the Kudus community in the 2018 governor election. This research uses the theory of voter behavior as a source of guidance to answer the problems raised. This research uses descriptive quantitative research methods, namely the search for answers using questionnaires with the Multistage Random Sampling method or multi-stage random samples by taking 100 samples from 611,486 population. The results of this study, theoretically, Kudus Regency voters are sociological voters, namely a person's preferences that are influenced by their social background. The social characteristics referred to in this case are based on organizational affiliation between voters and candidates, besides that the most determining their choice is based on kinship factors such as family, friendship, patrons (Kyai), and 42% of voters choose because of the figure / image of the candidate and kinship ties. The GP-TY victory, which was supported by sociological voters, was strengthened by the presence of a charismatic kyai figure, KH. Maimoen Zubair (caretaker of Al-Anwar Sarang Rembang) who wrote a letter of instruction to support GP-TY to the alumni network of nest students called HIMMA (Himpunan Mutakharrijin Mutakharrijat Al-Anwar). Thus, although many of the nest students are affiliated with PKB, they did not vote for the pair promoted by PKB